KEPASTIAN HUKUM BERLAKUNYA POST-NUPTIAL AGREEMENT PADA PERKAWINAN CAMPURAN (STUDI KASUS PENETAPAN PENGADILAN AGAMA JAKARTA BARAT NO.073/PDT.P/2017/PA.JB) - Megarini Adila Putri Lubis (2021)
Marriage agreements in mixed marriages are done to provide legal certainty for husband and wife related to ownership of assets raised by the couple during marriage period. After the Constitutional Court Decision Number 69/PUU-XIII/ 2015 is issued, the marriage agreement can be made at time after the marriage is held. The Constitutional Court Decision Number 69/PUU-XIII/2015 provides a constitutional interpretation in Article 29 Paragraph (3) that the marriage agreement takes effect from the time the marriage takes place, except in case other things are stipulated in the marriage agreement. On the Stipulation No. 073/PDT.P/2017/PA.JB, Judge with his consideration has a different opinion that the marriage agreement after marriage comes into effect only after this stipulation is made. In this case there is a legal inconsistency in the legal interpretation of the Judges and the Constitutional Court Decision No.69 / PUU-XIII / 2015. The aims of this study are to determine the arrangement of agreements regarding to law in Indonesia and to perceive the legal certainty of the entry into force of the post-nuptial agreement (Case Study of Determination No. 073/PDT.P/ 2017/PA.JB). This study used a juridical normative research method with the Law approach and the case approach. It was carried out by literature study. This study resulted in the findings that, first, the marriage agreement is regulated based on positive law in Indonesia, consisting of Articles 139-154 of the Civil Code, Article 29 UUP, Articles 42-52 KHI, and the Constitutional Court Decision Number 69/ PUU-XIII/2015. Second, it was suggested that there was no legal certainty in Stipulation No. 073/PDT.P/2017/PA.JB due to differences in the interpretation of the Judges and those stipulated in the Constitutional Court Decision regarding the entry into force of the marriage agreement.